Genetic and Environmental Influences on Motor Function: A Magnetoencephalographic Study of Twins - Araki, Toshihiko (Frontiers Media S.A., 2014)
To investigate the effect of genetic and environmental influences on cerebral motor function, we determined similarities and differences of movement-related cortical fields (MRCFs) in middle-aged and elderly monozygotic (MZ) twins. MRCFs were measured using a 160-channel magnetoencephalogram system when MZ twins were instructed to repeat lifting of the right index finger. We compared latency, amplitude, dipole location, and dipole intensity of movement-evoked field 1 (MEF1) between 16 MZ twins and 16 pairs of genetically unrelated pairs. Differences in latency and dipole location between MZ twins were significantly less than those between unrelated age-matched pairs. However, amplitude and dipole intensity were not significantly different. These results suggest that the latency and dipole location of MEF1 are determined early in life by genetic and early common environmental factors, whereas amplitude and dipole intensity are influenced by long-term environmental factors. Improved understanding of genetic and environmental factors that influence cerebral motor function may contribute to evaluation and improvement for individual motor function.